Cross-border acquisitions and shareholder wealth: Evidence from the energy industry in Central and Eastern Europe - Tomasz P. Bednarczyk; Dirk Schiereck; Hendrik N. Walter (Journal for East European Management Studies, 2010)
We look at the wealth generated for shareholders of energy assets in Central and Eastern Europe (CEE) by the announcement of cross-border mergers or acquisitions involving a bidder from a Western industrialized country between 1995 and 2005. The impact on both the performance improvements at the firm level as well as on an industry and economic level of foreign ownership of the energy assets in CEE are discussed. The main driver behind the positive effect is the industrial relatedness in acquiring CEE energy assets, while bidder experience and the relative size of the acquired stake do not impact the results significantly. – – Wir betrachten die Werteffekte nach Ankündigungen von grenzüberschreitenden Akquisitionen von Unternehmen der Energiewirtschaft in Mittel- und Osteuropa zwischen 1995 und 2005, bei denen jeweils ein westeuropäischer Bieter einbezogen war. Sowohl der Einfluss auf die Unternehmensperformance als auch auf den ausländischen Anteilsbesitz auf Branchenebene wird diskutiert. Als Haupttreiber des positiven Werteffekts kann die Branchenbeziehung ausgemacht werden, während M&A-Erfahrung und die relative Größe des Kaufobjekts keinen signifikanten Einfluss aufweisen.
Keywords: 650; cross-border mergers and acquisitions; capital market integration; corporate control; energy industry